Análisis de la reciente modificación al índice bursátil inmobiliario en la bolsa mexicana de valores - Solís Tepexpa, Sergio; Universidad Autónoma Metropolitana de México (Universidad Santo Tomás seccional Bucaramanga, 2018)
After the subprime crisis in the United States, the Mexican housing construction market suffered a major fall from the over-indebtedness of its bidders, which was reflected in the unfavorable evolution in Habita Index or IH.MX. In this scenario was carried out a restructuring of the sample of this indicator, with a view to an expected improvement in it. When analyzing the behavior of the volatility of the indicated index, through the GARCH methodology, in the period December 2015 February 2017, a high degree of volatility is still appreciating. This points to the systemic view of the Economy, which goes beyond of the merely technical and/or fundamental elements, as stated by the theory of efficient markets, being insufficient to explain the above.